2016
DOI: 10.1142/s0129065716500295
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Detection of Starting and Stopping During Gait Cycle

Abstract: Walking is for humans an essential task in our daily life. However, there is a huge (and growing) number of people who have this ability diminished or are not able to walk due to motor disabilities. In this paper, a system to detect the start and the stop of the gait through electroencephalographic signals has been developed. The system has been designed in order to be applied in the future to control a lower limb exoskeleton to help stroke or spinal cord injured patients during the gait. The brain-machine int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 27 publications
1
36
0
3
Order By: Relevance
“…MRCP corresponding to self-paced movement is known as Bereitschafts Potential (BP), and it is characterized by a slow decrease in EEG amplitude over the primary motor cortex within at least 0.5 s preceding the movement initiation. On the other hand, ERD is defined as a decrease in spectral power 0.5-2 s before movement onset reported most in the mu (8)(9)(10)(11)(12) and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) frequency bands of the brain wave [16][17][18]. The limits of the frequency bands may differ across different authors.…”
Section: Introductionmentioning
confidence: 99%
“…MRCP corresponding to self-paced movement is known as Bereitschafts Potential (BP), and it is characterized by a slow decrease in EEG amplitude over the primary motor cortex within at least 0.5 s preceding the movement initiation. On the other hand, ERD is defined as a decrease in spectral power 0.5-2 s before movement onset reported most in the mu (8)(9)(10)(11)(12) and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) frequency bands of the brain wave [16][17][18]. The limits of the frequency bands may differ across different authors.…”
Section: Introductionmentioning
confidence: 99%
“…Otros filtros de interés son los filtros espaciales que se basan en eliminan la influencia de los otros electrodos, como el filtro Laplaciano o el de referencia común media (CAR: Common Average Reference) [17].…”
Section: Preprocesamientounclassified
“…• Potenciales evocados: Las características extraídas de la señal de EEG en este tipo de BMI son aquellas producidas automáti-camente por el cerebro como consecuencia de un estímulo externo [17]. Uno de los más conocidos potenciales evocados es el P300.…”
Section: Selección De Característicasunclassified
“…Through the analysis of the above clinical researches, it is found that the rehabilitation effect of exoskeleton robot varies in different stages of stroke and different joints of limbs [13][14][15][16] , the key to improving its clinical effect lies in the mechanism design and software control [17][18][19][20] , and there is no mature research paradigm of gait training assisted by exoskeleton robot for stroke patients [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%